Hospital admissions and mortality in the 15 years after a first-time hospital contact with an alcohol problem: a prospective cohort study using the entire Danish population. (23rd July 2019) - Askgaard, Gro; Leon, David A; Deleuran, Thomas; Tolstrup, Janne S
Abstract: Background: Potential benefits of preventing continued alcohol intake in individuals presenting at the hospital with an alcohol problem can be highlighted by studying their excess risk of subsequent morbidity and mortality. Methods: All Danish residents with a first-time hospital contact with alcohol problems (intoxication, harmful use or dependence) in 1998–2002 were followed through 2012 using healthcare registries. We compared their cause-specific rates of hospital admission and mortality to the expected rates derived from the general population by calculating standardized incidence rate ratios. Results: The 26 716 men and 12 169 women who were hospitalized with alcohol problems (median age 44 years) had more than 10 times the rate of subsequent admission to psychiatric departments and three times the rate of subsequent admission to somatic departments compared with the general population. In particular, the hospital admission rates for gastroenterological disease and injuries were high. The cumulative all-cause 10-year mortality risk was 29% [95% confidence interval (CI), 28–30] in men and 26% (95% CI, 24–27) in women with alcohol problems. The ratios of observed to expected death rate for all-cause mortality were 4.0 (95% CI, 3.8–4.1) in men and 4.3 (95% CI, 4.0–4.7) in women and, for causes of death fully attributable to alcohol, 16 (95% CI, 15–17) in men and 33 (95% CI, 29–38) in women. Conclusions: Individuals hospitalized with alcohol problems have much higher rates of subsequent alcohol-related hospital admission and mortality than the general population. Increased focus on preventing continued alcohol consumption in these individuals may reduce their subsequent morbidity and mortality.